2008
DOI: 10.1007/bf03086122
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro B-type natriuretic peptide levels predict newly detected atrial fibrillation in a population-based cohort

Abstract: Background. B-type natriuretic peptide (BNP) is secreted from cardiomyocytes and may reflect haemodynamic abnormalities predisposing to atrial fibrillation (AF). We aimed to investigate whether N-terminal pro BNP (NT-proBNP) is associated with newly detected AF in subjects obtained from the general population. Methods. From the PREVEND programme (n=8592), we selected all subjects with an available baseline and four-year electrocardiogram and NTproBNP levels at baseline. We excluded subjects with AF at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
4
21
1
1
Order By: Relevance
“…We did not find any significant association between PWD and other wellknown risk factors of AF, including age. Although amino-terminal proBNP levels have been suggested to predict newly detected AF in subjects in the general population, 38 there was no significant association between proBNP level and PWD in our study. Perindopril dose did not influence PWD in our study.…”
Section: Resultscontrasting
confidence: 95%
“…We did not find any significant association between PWD and other wellknown risk factors of AF, including age. Although amino-terminal proBNP levels have been suggested to predict newly detected AF in subjects in the general population, 38 there was no significant association between proBNP level and PWD in our study. Perindopril dose did not influence PWD in our study.…”
Section: Resultscontrasting
confidence: 95%
“…These findings are in accordance with the results of previous studies (11,17,18,23,24). In previous studies, structural heart disease such as hypertension and coronary artery disease were significantly associated with NT-proBNP or BNP (10,11,18,23,24). However, a similar association was not found in our study and another study (12).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that NT-proBNP levels can be associated with AF in patients with normal LV systolic function (10)(11)(12)(13)(14)(15)(16)(17)(18). These studies included the patients with paroxysmal, persistent or chronic AF.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of individuals at risk for AF remains a challenge, though. Therefore, risk stratification based on clinical, biomarkers and echocardiographic parameters to define patients who are at risk for AF has been studied extensively [8][9][10][11][12][13][14][15][16][17][18] . With its ability to identify or exclude abnormalities in cardiac structure and function, echocardiography could be useful for prediction of future…”
Section: Introductionmentioning
confidence: 99%